Inovasi Model Pembelajaran Bahasa Indonesia di Sekolah Dasar - Ghufron, Syamsul (Universitas Pendidikan Ganesha, 2024)
The background of this study is the need for an innovative learning model to improve the quality of Indonesian Language learning at the elementary level. This study aims to analyze the innovation of the Indonesian Language learning model (IMPBI) in elementary schools. This study is classified as a systematic literature review with a focus on the topic of IMPBI in elementary schools. Data sources are taken from Google Scholar in the form of relevant articles or research reports. Data collection was carried out using the keywords